EJERCICIO Nº 10

f ( x) = 2 + 2
1

1 x

1 x

−1 − (−1) − x f ' ( x) = 2 · 2 x · Ln 2 + · 2 · Ln 2 = x x2

1

NO PASES A LA SIGUIENTE HOJA HASTA QUE NO HALLAS ENTENDIDO ÉSTA. INTENTA ACABAR EL EJERCICIO ANTES DE VER LA SOLUCIÓN

EJERCICIO Nº 10

f ( x) = 2 + 2
1

1 x

1 x

−1 − (−1) − x f ' ( x) = 2 · 2 x · Ln 2 + · 2 · Ln 2 = x x2 1 1 − −1 x 1 · 2 · Ln 2 + 2 · 2 x · Ln 2 = 2 x x

1

NO PASES A LA SIGUIENTE HOJA HASTA QUE NO HALLAS ENTENDIDO ÉSTA. INTENTA ACABAR EL EJERCICIO ANTES DE VER LA SOLUCIÓN

EJERCICIO Nº 10

f ( x) = 2 + 2
1

1 x

1 x

−1 − (−1) − x f ' ( x) = 2 · 2 x · Ln 2 + · 2 · Ln 2 = x x2 1 1 − −1 x 1 · 2 · Ln 2 + 2 · 2 x · Ln 2 = 2 x x 1 1 −   1 x · Ln 2 ·  − 2 + 2 x  =   x2  

1

NO PASES A LA SIGUIENTE HOJA HASTA QUE NO HALLAS ENTENDIDO ÉSTA. INTENTA ACABAR EL EJERCICIO ANTES DE VER LA SOLUCIÓN

EJERCICIO Nº 10

f ( x) = 2 + 2
1

1 x

1 x

−1 − (−1) − x f ' ( x) = 2 · 2 x · Ln 2 + · 2 · Ln 2 = x x2 1 1 − −1 x 1 · 2 · Ln 2 + 2 · 2 x · Ln 2 = 2 x x 1 1 −   1 · Ln 2 ·  − 2 x + 2 x  =   x2   1  Ln 2  − 2 x + 1  = · 1  x2     2x 

1

NO PASES A LA SIGUIENTE HOJA HASTA QUE NO HALLAS ENTENDIDO ÉSTA. INTENTA ACABAR EL EJERCICIO ANTES DE VER LA SOLUCIÓN

EJERCICIO Nº 10

f ( x) = 2 + 2
1

1 x

1 x

−1 − (−1) − x f ' ( x) = 2 · 2 x · Ln 2 + · 2 · Ln 2 = x x2 1 1 − −1 x 1 · 2 · Ln 2 + 2 · 2 x · Ln 2 = 2 x x 1 1 −   1 · Ln 2 ·  − 2 x + 2 x  =   x2   1   Ln 2  1  x · −2 + 1  = x2    2x   2   Ln 2  − 2 x + 1  ·  1 x2   x  2 
SOLUCIÓN:
2  Ln 2  − 2 x + 1 f ' ( x) = 2 ·  1 x  2x 

1

    